First Report With Medium-term Follow-up of Intestinal Transplantation for Advanced and Recurrent Nonresectable Pseudomyxoma Peritonei. Issue 5 (5th May 2023) - Reddy, Srikanth; Punjala, Sai Rithin; Allan, Philip; Vaidya, Anil; Borle, Deeplaxmi P.; Geiele, Henk; Udupa, Venkatesha; Smith, Alison; Vokes, Lisa; Vrakas, Georgios; Mohamed, Faheez; Dayal, Sanjeev; et al.
Abstract : Objective: To report our experience with the combination of radical surgical excision and intestinal transplantation in patients with recurrent pseudomyxoma peritonei (PMP) not amenable to further cytoreductive surgery (CRS). Background: CRS and heated intraoperative peritoneal chemotherapy are effective treatments for many patients with PMP. In patients with extensive small bowel involvement or nonresectable recurrence, disease progression results in small bowel obstruction, nutritional failure, and fistulation, with resulting abdominal wall failure. Methods: Between 2013 and 2022, patients with PMP who had a nutritional failure and were not suitable for further CRS underwent radical debulking and intestinal transplantation at our centre. Results: Fifteen patients underwent radical exenteration of affected intra-abdominal organs and transplantation adapted according to the individual case. Eight patients had isolated small bowel transplantation and 7 patients underwent modified multivisceral transplantation. In addition, in 7 patients with significant abdominal wall tumor involvement, a full-thickness vascularized abdominal wall transplant was performed. Two of the 15 patients died within 90 days due to surgically related complications. Actuarial 1-year and 5-year patient survivals were 79% and 55%, respectively. The majority of the patients had significant improvement in quality of life after transplantation. Progression/recurrence of disease was detected in 91% of patients followed up for more than 6 months. Conclusion: Intestinal/multivisceral transplantation enables a more radical approach to the management of PMP than can be achieved with conventional surgical methods and is suitable for patients for whom there is no conventional surgical option. This complex surgical intervention requires the combined skills of both peritoneal malignancy and transplant teams.